Significant progression of load on the musculoskeletal system with extremely high loads, with rapid weekly weight gains, using the Anatoly Gravitational System, in a 10-week training period - Burke, D. T.; Tran, D.; Cui, D.; Burke, D. P.; Al-Adawi, S.; Dorvlo, A. S. S. (Open Access Journal of Sports Medicine, 2014)
In an age of increasing numbers of lifestyle diseases and plasticity of longevity, exercise and weight training have been increasingly recognized as both preventing and mitigating the severity of many illnesses. This study was designed to determine whether significant weight-lifting gains could be realized through the Anatoly Gravitational System. Specifically, this study sought to determine whether this once-weekly weight-training system could result in significant weekly strength gains during a 10-week training period. A total of 50 participants, ranging in age from 17 to 67 years, completed at least 10 weekly 30-minute training sessions. The results suggest participants could, on average, double their weight-lifting capacity within 10 sessions. This preliminary study, which would require further scrutiny, suggests the Anatoly Gravitational System provides a rather unique opportunity to load the musculoskeletal system with extremely high loads, with rapid weekly weight gains, using only short weekly training sessions. More studies are warranted to scrutinize these findings.